Reflections on confidentiality as ethics in the professional practice of social workers: https://doi.org/10.53809/2021-01-TS-n.1-49-66 ("Temas Sociais" Journal, 2021)
The practice of social workers has been faced with complex ethical problems and dilemmas, especially regarding the principle of confidentiality. As a social and human relations profession confidentiality is a unique and irreplaceable asset that has gained prominence not only from a normative point of view, but from an ethical point of view. In this article, we argue that professionals ensure confidentiality by promoting people's rights but face some challenges in their professional practice that are not always easy to overcome. It is intended to reflect on the principle of confidentiality from the ethical normative point of view. To achieve this goal, we take as reference the standards and ethical principles of the code of ethics of the International Federation of Social Workers, the International Association of Schools of Social Workers and the association of social work professionals and some practical examples that were revealed in the literature review.
Keywords: social work; confidentiality; secrecy; profession